The Turbulent Years of the Greek Catholic Education System After 1989 - Ágnes Inántsy-Pap; Barnabás Szilágyi (Különleges Bánásmód)
The present study focuses on the revival of denominational education in Hungary after the nationalisation of schools in 1948.  It focuses on the decisive role played by Act IV of 1990, which created the legal and infrastructural conditions for the independent operation of denominational educational institutions. The law guaranteed freedom of religious belief and assembly, fostering the emergence of a pluralistic society that recognised the role of Churches in education. The analysis explores the relationship between social attitudes towards church schools and the political situation after the change of regime, and also examines the school takeovers in the Greek Catholic Metropolian Church. Surveys show that the reopening of church schools has received considerable public support, reflecting a nostalgic longing for pre-nationalisation educational values amid dissatisfaction with state education. At the same time, social divisions emerged, with some fearing the re-emergence of religious influence in education and others arguing for a greater role for the churches. The case study on the re-engagement of the Greek Catholic Church in education highlights difficulties such as funding and the need for consensus on educational values among stakeholders. The research draws on interviews with key figures in the Greek Catholic community and relevant literature to illustrate the nuanced dynamics at play during the transition period. Ultimately, this study contributes to our understanding of how historical context, legal frameworks and social attitudes shape contemporary educational policy in Hungary.